Reading as a Productive Skill and Visual Response as a Reading Strategy - Nejla Kalajdžisalihović (Društvene i Humanističke Studije, 2022)
The paper discusses the visual response to text as a reading strategy employed to determine which parts or main ideas of the text the reader focuses on while reading. It starts with an assumption that every reading is a unique experience to which readers bring their previous experiences, cultural and social backgrounds, as well as general or specific knowledge. Therefore, the aim of the paper is to provide a better insight into active reading (Carillo 2017) and present results of a case study that, through visual responses to reading, also addresses text processing in a multimodal setting. The methodological framework comprises a visual response task that requires that the readers draw or sketch a visual interpretation of the text. In this way, sketching in response to reading is used as a complementary component and a visualization tool in the reading process (Wilhelm 1995; Fernandes 2018). Based on the results of the research, it is proposed that visual response to reading can be used to enhance multimodal creativity, and vocabulary acquisition and fully immerse readers in the reading process.